2002
DOI: 10.1016/s0022-2275(20)30183-8
|View full text |Cite
|
Sign up to set email alerts
|

Induction of monocyte differentiation and foam cell formation in vitro by 7-ketocholesterol

Abstract: Oxidized LDL (OxLDL) is composed of many potentially proatherogenic molecules, including oxysterols. Of the oxysterols, 7-ketocholesterol (7-KC) is found in relatively large abundance in OxLDL, as well as in atherosclerotic plaque and foam cells in vivo. Although there is evidence that 7-KC activates endothelial cells, its effect on monocytes is unknown. We tested the hypothesis that 7-KC may induce monocyte differentiation and promote foam cell formation. THP-1 cells were used as a monocyte model system and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…We decided to study the effects and mechanisms of action of SA in cells of retinal origin because of the potential therapeutic role of SA in ocular diseases [12,13,24]. We used a primary immortalized RPE cell line that recapitulates well RPE function and physiology [57,58], as well as ARPE19 and RF6/A cell lines to show lack of toxicity of SA up to 20 µM, which is a higher dose than the one used in vitro and in vivo to show effects [11][12][13]15,16,24,42]. These data were in agreement with reports showing the lack of toxicity in vivo, in hamsters or rats fed with an SO-enriched diet [27,41] or in vitro in differentiated adipocytes [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to study the effects and mechanisms of action of SA in cells of retinal origin because of the potential therapeutic role of SA in ocular diseases [12,13,24]. We used a primary immortalized RPE cell line that recapitulates well RPE function and physiology [57,58], as well as ARPE19 and RF6/A cell lines to show lack of toxicity of SA up to 20 µM, which is a higher dose than the one used in vitro and in vivo to show effects [11][12][13]15,16,24,42]. These data were in agreement with reports showing the lack of toxicity in vivo, in hamsters or rats fed with an SO-enriched diet [27,41] or in vitro in differentiated adipocytes [34].…”
Section: Discussionmentioning
confidence: 99%
“…These deposits are composed of proteins, mineral and lipids [10], one which, 7-ketocholesterol (7KCh), is a central component associated with AMD pathology [11]. 7KCh is an oxysterol that has been related to several degenerative diseases, including AMD [12][13][14], atherosclerosis [15][16][17][18], Parkinson's [19,20] and Alzheimer's disease [21][22][23]. It has been demonstrated that 7KCh promotes an inflammatory and a cytotoxic response [14,24,25], but it also promotes cell arrest and cell death by different molecular mechanisms still not completely decoded [25].…”
Section: Introductionmentioning
confidence: 99%
“…Serum oxidized sterols (oxysterols) are a major component in oxidized LDL and are thought to mediate its lipotoxic effects. Oxysterols, such as 7-ketocholesterol (7-KC), are abundant in advanced atherosclerotic lesions [28]. Therefore, we measured the levels of free 7-KC levels in the plasma of subjects and observed that circulating 7-KC levels were significantly higher in subjects with diabetes compared to subjects without diabetes (Figure 6D).…”
Section: Expression Of Cd36 and Er Stress Indicators In Carotid Plaques From Subjects With And Without Diabetesmentioning
confidence: 99%
“…The migration and proliferation of smooth muscle cells are induced by growth factors (Guardiola et al., 1996). Oxidized low‐density lipoprotein (oxLDLs) that stimulate monocyte differentiation lead to the generation of foam cells, the proliferation of smooth muscle cells, production of elastin and collagen, and deposition of calcium (Guardiola et al., 1996; Hayden et al., 2002). These factors together trigger the formation of atherosclerotic plaques, which gradually narrow vessel lumen and thus cause thrombosis, eventually leading to heart attack and stroke (Chisolm & Steinberg, 2000).…”
Section: Health Implications Of Dietary Cops and Interventions Using Natural Compoundsmentioning
confidence: 99%